Magmatic fingerprints of subduction initiation and mature subduction: numerical modelling and observations from the Izu-Bonin-Mariana system - Ritter, Sandrine; Balázs, Attila; Ribeiro, Julia; Gerya, Taras (Frontiers in Earth Science, 2024)
Understanding the formation of new subduction zones is important because they have been proposed as the main driving mechanism for plate tectonics and they are crucial for geochemical cycles on Earth. However, the conditions needed to facilitate subduction zone initiation and the associated magmatic evolution are still poorly understood. Using a natural case study, we conducted a series of high-resolution 2D petrological-thermomechanical (i2VIS) subduction models assuming visco-plastic rheology. We aim to model the initiation and early stage of an intra-oceanic subduction zone connected to the gravitational collapse of a weak transform zone and compare it to the natural example of the Izu-Bonin-Mariana subduction zone. We also analysed the influence of low convergence rates on magmatic evolution. We propose a viable transition from initiation to mature subduction zone divided into distinct stages that include initiation by gravitational collapse of the subducting slab, development of a near-trench spreading centre, gradual build-up of asthenospheric mantle return flow, and maturation of a volcanic arc. We further show that mantle flow variations and shear instabilities, producing thermal perturbations and depleted interlayers, influence the temporal and spatial distribution of asthenospheric mantle composition and fertility in the mantle wedge. Our modelling results are in good agreement with geological and geochemical observations of the early stages of the Izu-Bonin-Mariana subduction zone.